REVISITING HOUSEHOLD OBJECTS:THEIR CONTINUITY IN GANDHARA ART (Contemporary Journal of Social Science Review, 2025)
Gandhāra or the ancient Peshawar valley is a blend of diverse cultures through artistic expression, represented in the Stone and stucco sculptures. The representation ranges from common social and domestic activities to the religious and princely phenomenon. On many friezes and relief panels, one may observe the wrestlers, musicians, and dancers. Additionally, the artists carved several religious ideas and beliefs on various relief panels that throw light on their socio-political, socio-economic and religious facets of their civilization. Their daily life activities are carved in such a way that reveals their skill and commitment to their work. Even with the passage of times these activities and objects carved are still practiced for centuries with minor modifications or alterations.Gandhāra was invaded by many foreign nations. All of them have left their impact on the local traditions and cultures e.g. food, dress, Household objects, Jewellery, Furniture, Music and Sports etc. This paper concentrates on the household objects that carved in the different relief panels of Buddhist art. The influence of past traditions is still clearly visible in present society. Although they have lost their original form, a glimpse of the past can still be easily seen in them. As for instance, in different relief panels, the artists of Gandhāra carved different household objects are carved. The same objects are still in use in Peshawar valley with minor changes like cup, pitcher, Tub etc.